2017
DOI: 10.7150/jca.18729
|View full text |Cite
|
Sign up to set email alerts
|

Association between PD-L1 Expression on Tumour-Infiltrating Lymphocytes and Overall Survival in Patients with Gastric Cancer

Abstract: Purpose Targeting of the PD-1/PD-L1 signalling pathway is a promising treatment strategy in several cancers. The aim of this study was to assess the expression of PD-L1 on tumour cells and tumour-infiltrating lymphocytes (TILs) in gastric cancer (GC) and its prognostic impact.Materials and Methods A total of 240 patients who were diagnosed with GC at Sun Yat-sen University Cancer Centre (SYSUCC) from May 2008 to December 2013 were included in this study. PD-L1 expression was detected by immunohistochemistry (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 25 publications
4
21
0
3
Order By: Relevance
“…However, the relationship between PD-L1 expression and the prognosis remains controversial in GC. Many researches showed that PD-L1 expression had a negative impact on patient survival [24][25][26][27], but some studies indicated that PD-L1 positivity was associated with favorable outcomes [16,28]. In our study, PD-L1 expression in GC was related to some adverse clinicopathological characteristics, which was observed more frequently in advanced GCs occurred in the older patients and with bigger tumor size.…”
Section: Pd-l1 Expression In Gastric Cancermentioning
confidence: 49%
“…However, the relationship between PD-L1 expression and the prognosis remains controversial in GC. Many researches showed that PD-L1 expression had a negative impact on patient survival [24][25][26][27], but some studies indicated that PD-L1 positivity was associated with favorable outcomes [16,28]. In our study, PD-L1 expression in GC was related to some adverse clinicopathological characteristics, which was observed more frequently in advanced GCs occurred in the older patients and with bigger tumor size.…”
Section: Pd-l1 Expression In Gastric Cancermentioning
confidence: 49%
“…As only 25 patients were PD‐L1‐positive, these may have limited the survival analysis. Furthermore, this variability in reported outcomes might be influenced in part by the patient cohort, since we had 55.1% of GCs staged as I/II and high PD‐L1 levels seems to be related to more advanced stages …”
Section: Discussionmentioning
confidence: 95%
“…In general, studies have small populations and few meta-analyses have shown a correlation between PD-L1 and prognosis. 25,26,35,36 Some authors showed that PD-L1-positive expression was associated to poor prognosis in advanced GC, 37,38 whereas other studies proposed that increased PD-L1 expression are related to a better prognosis. 34,39 Still, some authors have shown no impact on survival.…”
Section: Several Researchers Have Demonstrated That Pd-l1 Expression Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Em geral, os estudos envolvem casuísticas pequenas e poucas metaanálises apresentam associação entre PD-L1 e prognóstico 80,81,123,127. Alguns autores mostraram que a positividade para PD-L1 está associada a pior prognóstico no CG avançado,128,129 enquanto outros propõe que o aumento da expressão de PD-L1 relaciona-se a melhor prognóstico 83,87. Ainda assim, alguns autores não mostraram nenhum impacto na sobrevida 42,109.…”
unclassified